2017
DOI: 10.1055/s-0037-1602759
|View full text |Cite
|
Sign up to set email alerts
|

One versus Two Venous Anastomoses in Microvascular Upper Extremity Reconstruction

Abstract: Background Free tissue transfers are routinely performed for reconstruction of the upper limb. Main complication in free flap surgery still stems from vascular compromise and many technical controversies exist regarding the technical details of how to perform the microvascular anastomosis. This study evaluates outcomes regarding the execution of one versus two venous anastomoses for upper limb reconstruction. Methods In this study, 79 patients underwent 86 free anterolateral thigh (ALT) or groin fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Some studies have also suggested significantly reduced flap failure and venous thrombosis after anastomosis involving two veins compared with one. 16,17 However, Ehrl et al 18 showed that flap survival is independent of the number of venous anastomoses. This study maintained the number of veins, but changed the positions of venous drainage, to assess the effects of venous drainage position on arterial blood supply and venous return within the flap, providing a theoretical basis for the clinical management of conjoined flaps.…”
mentioning
confidence: 99%
“…Some studies have also suggested significantly reduced flap failure and venous thrombosis after anastomosis involving two veins compared with one. 16,17 However, Ehrl et al 18 showed that flap survival is independent of the number of venous anastomoses. This study maintained the number of veins, but changed the positions of venous drainage, to assess the effects of venous drainage position on arterial blood supply and venous return within the flap, providing a theoretical basis for the clinical management of conjoined flaps.…”
mentioning
confidence: 99%